Evaluation of the Rationality of OTC (Over The Counter) Drug Self-Medication in Patients in Pasaman Barat District Pharmacy - Budi Setiawan; Renatalia Fika; Mevy Trisna; Nurhida Yanti (Science Midwifery, 2022)
Self-medication is simply a person's attempt to treat symptoms of illness or disease without consulting a doctor first. Self-medication also means treating all complaints about oneself with medicines purchased directly at pharmacies or drug stores on their initiative without a doctor's prescription. OTC (Over The Counter) drugs are medicines that can be purchased without a prescription, namely over-the-counter and limited over-the-counter drugs, including fever-reducing drugs, pain relievers and inflammation relievers, cough medicines, cold medicines, ulcer medicines, diarrhea medicines, and skin medicines. The use of drugs in self-medication is carried out correctly to ensure the accuracy, rationality, and safety of drug use in self-medication. This study aimed to determine the demographic data characteristics of self-medication patients, the rationality of self-medication, and the influence of patient demographic data characteristics on rationality in OTC (Over Counter) drug self-medication patients. This study used a cross-sectional method. As many as 100 respondents aged 18-60 who self-medicated OTC (Over Counter) drugs at the West Pasaman District Pharmacy were involved in this study. Data collection was carried out using a questionnaire. Data were analyzed using Statistical Product And Servicer Solution (SPSS) 23. The results of this study showed that the majority of respondents who self-medicated OTC (Over Counter) drugs were 58% women, 63% of the age group 18-60 years, the last education group was low ( SD, SMP, SMA) by 77% and the non-PNS/non-private employee group is 82%. Respondents who used self-medication rationally were quite large, namely 86%. The factor that influences self-medication is age. While gender, education, and occupation do not affect self-medication